(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. Today the chemical industry provides the expanding of the raw material base in many industries from construction to pharmaceutical and food industries. In developed countries the chemical industry is developing at an accelerated rate due to its high scientific intensity and innovative activity and under the influence of NTP. The purpose of the article is to determine the peculiarities of production of chemicals and chemical products development and its role in the national economy of Ukraine. Results. In 2018 the production of chemicals and chemical products ranked the seventh. In the period from 2010 till 2018 the chemical products sales tend to increase against this background of the sales volumes decreased in 2013 and 2016. In contrast to the absolute measurement the share of chemicals in total industrial production sales has a negative trend against the backdrop of minor upturns. In the chemical industry the number of personnel decreased annually reflecting the share of employees in the chemical industry among those employed in the industry. The reduction in the number of chemical enterprises has led to an increase in the number of unemployed, which in its turn has contributed to the increase in the number of migrant workers, mainly to the countries of Eastern and Western Europe as well as to the Russian Federation. Also, a significant drop in the production of basic chemicals is related to a significant increase in prices for raw materials, first of all, natural gas, as well as to the destruction of chemical enterprises and cooperative ties between enterprises in the course of hostilities in the East of the country. The negative changes in the industry have led to an increase in imports of chemicals and chemical products from the PRC, which contributes to job creation and income growth in the Chinese chemical industry, but worsens the situation in the national economy of Ukraine and the labor market in particular. It is proved that by the income criterion, chemical production is not among the top ten industries in this indicator, and, in combination with harmful and hazardous working conditions at chemical enterprises, is not particularly attractive to the workforce. Comparing the growth rate of wages in chemical production with the consumer price index shows the inflation rate exceeding the wage growth rate in 2014-2015 and in 2016. Wage growth rates have exceeded inflation in the consumer market. Of concern is the structure of environmental costs in the chemical industry: out of the total amount spent on environmental protection, 95.2% is current costs, while capital investments aimed at upgrading the logistics and technology improvements make up only 4.8%, of which their cost of overhaul is 0.93%. The reduction of electricity and heat consumption in chemical production was not due to the introduction of resource-saving technologies but rather due to a reduction in production and sales as a consequence of the economic crisis. The magnitude of the correlation coefficients between variable capital investment and sales volume changes numerically, but the negative direction of the relationship remains. This indicates either the inefficiency of the invested funds use or the fact that the volume of sales is influenced by negative factors of greater power which negate the positive impact of capital investments. The absolute and relative indices of innovatively active enterprises in the chemical industry tend to decrease being the negative factor for development, Conclusions. One of the main results is that in order to provide a basis for the development of the chemical industry and to increase the efficiency of its activity, domestic chemical enterprises should give priority to the technical re-equipment of production and preparation of the production of innovative and competitive products. The basis for radical changes in the industries of the domestic industry is also the volume of capital investments. In order for a radical change in the environmental status of the industry to occur, the ratio of capital to operating costs should be prioritized in favor of capital investment. Development prospects are related to the improvement of the chemical enterprise resource structure; bringing the quality of products up to world standards, promoting the state (at the level of intergovernmental contacts) in entering new markets.